Implementation of Standards for Educators and Educational Personnel in Ukui District, Pelalawan Regency: Challenges, Field Conditions, and Strategies for Quality Improvement - Ayu Widiawati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The implementation of the Standard for Educators and Education Personnel (PTK) represents one of the most critical yet consistently underperforming components of the National Education Standards (SNP), particularly in remote and semi-urban areas such as Ukui Sub-district, Pelalawan Regency, Riau Province. This article provides an in-depth analysis of PTK standard implementation in Ukui Sub-district based on Government Regulation No. 57 of 2021 as amended by Government Regulation No. 4 of 2022 and Minister of Education Regulation No. 15 of 2018. Employing a descriptive case study approach reinforced by a systematic literature review, this research identifies that approximately 48.3% of educators in Ukui Sub-district do not meet the required S1/D-IV academic qualification, 61.7% have not obtained a teaching certificate, and the teacher-to-student ratio in several remote schools reaches 1:42, far exceeding the ideal standard of 1:28 for elementary schools. The analysis reveals four determinant factors: geographic isolation, low incentives, limited access to qualification improvement programs, and high rates of educator transfers. This article recommends a triple-helix collaboration model between local government, higher education institutions, and local communities as a sustainable and contextual strategy for improving PTK quality in Ukui Sub-district